Предмет: Математика,
автор: MixaMixa001
-0,9х-(0,6х+0,5у), если 3х+у=-0,2
Ответы
Автор ответа:
2
- 0,9х - (0,6х + 0,5у) = - 0,9х - 0,6х - 0,5у = - 1,5х - 0,5у = - (1,5х + 0,5у)
Если 3х + у = - 0,2
- (1,5х + 0,5у) = - 0,2 : 2 = - 0,1
- (- 0,1) = + 0,1
Ответ: 0,1.
Если 3х + у = - 0,2
- (1,5х + 0,5у) = - 0,2 : 2 = - 0,1
- (- 0,1) = + 0,1
Ответ: 0,1.
Похожие вопросы
Предмет: Физика,
автор: fkddkjd
Предмет: Русский язык,
автор: Vovarickbro
Предмет: Окружающий мир,
автор: 8764414
Предмет: Алгебра,
автор: Maksim2002hasanov